Genetic stability of cryopreserved MR 219 rice variety revealed by inter-retrotransposon amplified polymorphism (IRAP) / Nur Syamimi Mohamad Napis - Mohamad Napis, Nur Syamimi (2017)
Cryopreservation is widely applied by researchers to preserve genetic materials of a sample under a very low temperature using liquid nitrogen. Rice is possible to be stored and preserved under a very low temperature with the presence of cryoprotectants as to maintain cellular processes of the cells after cryopreservation. Two cryopreservation protocols which are dehydration and encapsulation-dehydration were used in this study to preserve genetic materials of an indica variety of MR 219 rice. The sterilised seeds of the MR 219 rice variety were cultured on MSO for four weeks to get aseptic seedlings as source of stem explants. Stem explants were, then cultured on MSO for two weeks. The stems (5 mm in length) were excised from 2-week-old plantlet derived from stem explants that were cultured on MSO medium. For dehydration method, stems were dehydrated for 219 minutes in a sterile Petri dish with 3.0 g silica gel to allow only 20 percent of water contained in the stems. O